2017
DOI: 10.1007/s13238-017-0393-7
|View full text |Cite|
|
Sign up to set email alerts
|

Oncogenic miR-19a and miR-19b co-regulate tumor suppressor MTUS1 to promote cell proliferation and migration in lung cancer

Abstract: MTUS1 (microtubule-associated tumor suppressor 1) has been identified that can function as a tumor suppressor gene in many malignant tumors. However, the function and mechanisms underlying the regulation of MTUS1 are unclear. In the present study, we reported that miR-19a and miR-19b (miR-19a/b) promote proliferation and migration of lung cancer cells by targeting MTUS1. First, MTUS1 was proved to function as a tumor suppressor in lung cancer and was linked to cell proliferation and migration promotion. Second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 36 publications
1
45
1
Order By: Relevance
“…MiR‐19a was reported to significantly regulate cell proliferation and migration. miR‐19a‐3p inhibits invasion, migration, and bone metastasis in prostate cancer, while in lung cancer, miR‐19a promotes cell proliferation and migration . miR‐19a‐3p also regulates the viability, migration, and invasion of trophoblast cells, because the overexpression of miR‐19a‐3p attenuated the inhibition of the cell viability, migration, and invasion under hypoxemia.…”
Section: Discussionmentioning
confidence: 99%
“…MiR‐19a was reported to significantly regulate cell proliferation and migration. miR‐19a‐3p inhibits invasion, migration, and bone metastasis in prostate cancer, while in lung cancer, miR‐19a promotes cell proliferation and migration . miR‐19a‐3p also regulates the viability, migration, and invasion of trophoblast cells, because the overexpression of miR‐19a‐3p attenuated the inhibition of the cell viability, migration, and invasion under hypoxemia.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, the present study is the first to provide evidence that PITX1 expression is modulated through miR-19a-3p in GC. miR-19a is frequently overexpressed, promotes cell proliferation and the epithelial to mesenchymal transition, and inhibits cell apoptosis in lung carcinoma [36,37], osteosarcoma stem cells [38], colorectal cancer [39][40][41][42], cell renal cell carcinoma [43], oral squamous cell carcinoma [44], hepatocellular carcinoma cells [45], pancreatic cancer [46], GC [47,48], cholangiocarcinoma [49], breast cancer [50], bladder cancer [51], medulloblastoma [52], and cervical carcinoma [53]. Our findings are consistent with these data because they provide evidence that miR19a is a key regulator of the multistep processes of cancer development.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…4 Accumulating evidence suggested that miRNAs play important roles in the initiation and progression of various human cancers including ovarian cancer. 5,6 miR-19a-3p is a member of the miR-17 to 92 clusters, its expression is frequently dysregulated and which is closely associated with proliferation, apoptosis, metastasis, and chemoresistance of various malignant tumors such as gastric cancer, 7,8 pancreatic cancer, 9 liver cancer, 10 lung cancer 11,12 and breast cancer. 13,14 It has been reported that miR-19a was highly expressed in ovarian cancer tissues and cell lines, and it promotes the growth of ovarian cancer cells.…”
Section: Introductionmentioning
confidence: 99%